Computational study of the structure and electronic circular dichroism spectroscopy of blue copper proteins - Do, Hainam; Deeth, Robert J.; Besley, Nicholas A. (American Chemical Society, 2013)
The calculation of the electronic circular dichroism (CD) spectra of the oxidised form of the blue copper proteins plastocyanin and cucumber basic protein and the relationship between the observed spectral features and the structure of the active site of the protein is investigated. Excitation energies and transition strengths are computed using multi reference configuration interaction, and it is shown that computed spectra based on coordinates from the crystal structure or a single structure optimised in quantum mechanics/molecular mechanics (QM/MM) or ligand field molecular mechanics (LFMM) are qualitatively incorrect. In particular, the rotational strength of the ligand to metal charge transfer band is predicted to be too small or have the incorrect sign. By considering calculations on active site models with modified structures it is shown that the intensity of this band is sensitive to the non-planarity of the histidine and cysteine ligands coordinated to copper. Calculation of the ultraviolet absorption and CD spectra based upon averaging over many structures drawn from a LFMM molecular dynamics simulation are in good agreement with experiment, and superior to analogous calculations based upon structures from a classical molecular dynamics simulation. This provides evidence that the LFMM force field provides an accurate description of the molecular dynamics of these proteins.